2014
DOI: 10.3390/s140304074
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Explosives in a Dynamic Marine Environment Using a Moored TNT Immunosensor

Abstract: Abstract:A field demonstration and longevity assessment for long-term monitoring of the explosive 2,4,6-trinitrotoluene (TNT) in a marine environment using an anti-TNT microfluidic immunosensor is described. The TNT immunosensor is comprised of a microfluidic device with 39 parallel microchannels (2.5 cm × 250 µm × 500 µm, L × W × D) fabricated in poly(methylmethacrylate) (PMMA), then chemically functionalized with antibodies possessing a high affinity for TNT. Synthesized fluorescence reporter complexes used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…To our knowledge, the present study is the only one that has employed passive sampling to detect munitions constituents released from a controlled source in an aquatic environment. Demonstration of an immunosensor installed on a field‐deployable platform for continuous sampling of TNT over a period of 18 h has been reported (Charles et al ). The sensor was calibrated to detect concentrations ranging from 1 to 100 μg/L, well above the range of detection for POCIS in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, the present study is the only one that has employed passive sampling to detect munitions constituents released from a controlled source in an aquatic environment. Demonstration of an immunosensor installed on a field‐deployable platform for continuous sampling of TNT over a period of 18 h has been reported (Charles et al ). The sensor was calibrated to detect concentrations ranging from 1 to 100 μg/L, well above the range of detection for POCIS in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrocellulose industry wastewater is highly toxic to the environment because it contains chlorophenols, chlorolignins, organic acids, acid resins, and dioxins [23,32], as well as high levels of organic matter and metal ions [22]. There are few studies analyzing the toxicity of nitrocellulose to aquatic organisms [37-39], but many studies reported the detrimental effects of other explosives, such as 2,4,6-trinitrotoluene (TNT), 1,3,5-Trinitroperhydro-1,3,5-triazine (RDX), and 1,3,5,7tetranitro-1,3,5,7-tetrazocane (HMX) [40][41][42][43][44][45][46].…”
Section: Cbmentioning
confidence: 99%
“…In addition to faster medical diagnostics [ 22 , 23 , 24 , 25 ], microfluidics is being applied in drugs of abuse testing [ 26 , 27 , 28 , 29 ], pollutant detection [ 30 , 31 , 32 , 33 , 34 ], combatting biowarfare [ 35 , 36 , 37 , 38 ] and also in laboratory routines in a research context, as described below.…”
Section: Microfluidics—from Small Benchtop Biosensors To High-thromentioning
confidence: 99%